Hybrid Napier - Grewia optiva based silvipastoral system for degraded bouldery riverbed lands in Doon Valley - Singh, Charan; Dadhwal, K.S. (Indian Journal of Agroforestry, 2020)
Present study was conducted during 1990 - 2000 at the Research farm (Selakui) of the Central Soil and Water Conservation Research and Training Institute, Dehradun to assess biomass productivity of Hybrid Napier - Grewia optiva based silvipastoral system in degraded land. The trial consisted of five treatments viz. Trees lopping + grass; Trees Pollarding + grass; Trees lopping only; Trees pollarding only; Only grass. The findings revealed that the survival of the hybrid Napier grass was significantly affected by the tree canopy management practices with highest grass survival (79.0%) under tree pollarding and least 9715) under tree lopping. The tree pollarding management practice also produced highest green fodder (260 q/ha) followed by grass alone. Over the years, biomass production declined in all treatments. It is concluded from the study that the pollarding + grass was the best treatment to obtain grass biomass from degraded lands followed by lopping + grass. Tree pollarding alone was the best technique for biomass production as compared with the canopy management practice in grass combinations.